Pengaruh Tingkat Kesehatan Keuangan Perusahaan Terhadap Harga Jual Saham Pada Perusahaan Otomotif yang Terdaftar di BEI - faisol, imam agus (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2016)
The purpose of this research to examine the influence of the level of financial health firm against the price of selling stock. The ratio that use in the research is profitability ratio that projected by ROA (Return On Asset), solvency problems that projected by DER (Debt To Equity Ratio), liquidity ratio that projected by CR (Current Ratio) and activity ratio that represent by asset turn over ratio as independent variable. While the stock price as dependen variable. The numbers of population use in this research is the automotive compenies that registered on the BEI. A sample of the methods used the purposive sampling, based on a sample of is obtained samples as much as 10 company. The data analysis that use in this research is analysis double regression. The results of the research shows that profitability variable that projected by return on asset (ROA) influential signifikan to the priceof salling stock. While the solvency problems variable that projected by debt to equity ratio (DER), liquidity (CR), and activity variable thar projected by asset turn over (ASST), does not have significant effect against the price of selling stock. The result of simultan statitics concluded that variable ROA, CR and ASST is simultaneosly not influential significant to price of selling stock.